Pengembangan Model Program Bantuan Layanan Belajar untuk Mengurangi Kesalahan Konsep Fisika pada Mahasiswa Program Studi Pendidikan Fisika FKIP Untad - Kamaluddin, Kamaluddin (Media Eksakta, 2009)
This research, planned a model of students support services program will provide some steps of remedial learning physics process which identify bad physics concepts known in students understanding, otherwise disturbed students thougts in studying physics. The objective of this research was to minimalized the mistakes understanding of students thought in physics. The research will be done during three fase, firsty, program compossing, secondly program testing, and thirdly validating. This services program will be provided by supported instruments. After observation, noticed that the physics misconcept thoughts of the students is 47%. It had decreased compare with their previous misconcepts thoughts before servicing as 71%. Eventhough this result isn’t coming optimum, at least this model program had given good value in minimalized misconcept (about 24% changes). This program needs several things to be reviced in gaining optimal result either in instrument and in services technique.